Child Health Indicators in Shareq Elneel Locality, Khartoum State, Sudan: A Cross-Sectional Study - Eljack, Ibrahim Awad; Hamedel Niel, Abdel Rahman Al-Asha (International Journal of Child Health and Nutrition, 2015)
Objective: To study child health status in Shareq Elneel Locality and its administrative units, Khartoum State, Sudan. Methods: A two stages cluster sampling, cross-sectional study was conducted in Shareq Elneel Locality and it is eight administrative units in Khartoum State, Sudan, in 2008. Questionnaires were collected from the caretakers of 5858 child under-5 years of age and anthropometric measurements were taken for children whose parents were consented. Results:69.4% of under 5 years children received the third dose of Poliomyelitis vaccine (Polio3) in the locality, 66.5% of under 5 years children received DPT3 vaccination in the locality, 71.9% of under 5 years children received Measles vaccination in the locality and 91.4% of the children under- 5 years in the locality had immunization card. There was evidence of a significant association between children under -5 measles vaccination and women’s highest level of school attended (P-Value= 0.04). Nearly one third of the under 5 children were moderately underweight and 16.2% them were severely underweight, More than one fifth of under 5 years children were moderately wasted, and 12% of children under -5 years old were severely wasted, 44.6% of children under -5 years of age were moderately stunted with obviously high percentage in the rural administrative units. More than one quarter of the children under- 5 years old were severely stunted and overweight prevalence of children under-5 years old in the locality was 14.6%. Only 21.4% of the children aged less than 2 years in the locality were exclusively breastfed. 27.5% of children under -5 years of age in the locality had diarrhea in the last 2 weeks preceding the survey, highest percentage found in the rural administrative units.6.5% of children under 5 years of age in the locality had fever in the last 2 weeks preceding the survey and nearly one third of under 5 years children in the locality had cough in the last 2 weeks preceding the survey. 87.9% of children targeted by vitamin A supplementation in the locality ever receive vitamin A dose. Conclusions: The study reveal pronounced variations among urban and rural administrative units in regard to many of the survey indicators. Immunization activities do not reach their target in almost all the times in the locality and there were other aspects of child health related to hygiene, poverty, malnutrition and health services like diarrhea, respiratory tract infections and malnutrition which need more consideration to be improved. Malnutrition prevalence was high. The rates of diarrhea and suspected pneumonia are somehow higher in the study area than previous studies figures. Reduce the pronounced variations among urban and rural administrative units in regard to Primary Health Care services and activities in order to improve many of the Child Health indicators in the rural areas. Use effective methods of health promotion and new attractive material of health education in the locality concerning the weak Child Health indicators.